Sustainable transport and the organisation of bus services in Manchester: Do markets, hierarchies or networks fail? - Sørensen, Claus Hedegaard; Gudmundsson, Henrik (Proceedings from the Annual Transport Conference at Aalborg University, 2008)
“Sustainable transport” has become a headline for transport planning and policy making around the world. While there are many different definitions of what Sustainable Transport means, it commonly includes efforts to improve the environmental performance of transport systems, and to promote alternative modes of transport to private cars, such as public transport. Public transport can be important for reducing environmental pressures in several ways. In this paper we focus only on the potential of bus transport services in cities for attracting travellers from cars. It is a basic assumption behind this paper that the ability of public bus transport to attract travellers from cars depends on how the bus sector is organised. By organisation we adopt an institutional point of view and consider basic modes of governance. Basic modes of governance include the forms “market”, “hierarchy” and “network” (Powell 1990). So-called New Public Management (NPM) reforms have changed the modes of governance of bus transport in several countries, including Denmark and the United Kingdom. Our focus is on how New Public Mangement Reforms have changed the mix of governance modes and thus may have influenced the ability of urban bus transport to attract travellers from cars. We focus on a particular case: Public bus transport in England, exemplified by Greater Manchester. England represents a situation where - compared to continental Europe including Denmark - the NPM reforms have been particularly radical. In no other European country the market forces has achieved a role as dominant as in England (outside London). We therefore assume that it is relevant to investigate the influence from the NPM reforms in this case, in order to discuss how the change in governance modes more generally enable or constrain the delivery of more sustainable transport patterns.